Branchial cysts: an unusual cause of a mediastinal mass: a case report. (December 2015) - Kotecha, Vihar; Muturi, Alex; Ruturi, Josiah
Abstract Introduction Complex embryological processes form the head and neck of humans. It is not flawless; remnants lead to sinuses or cysts, commonly in the head and neck region. Case presentation We present the a case of an 8-year-old boy, a primary school pupil, from rural Kenya with chronic cough, wheezing, difficulty in breathing and dyspnea on exertion. He was treated with antibiotics and antitubercular drugs without improvement prior to referral to our hospital. A computed tomography scan of his chest revealed a superior mediastinal mass extending into his neck. A diagnosis of a brachial cleft cyst was made and our patient underwent a successful excision of the mass through a median strenotomy and neck dissection. Conclusions Branchial cysts of the neck are common, accounting for 20% of pediatric neck masses. Usually they present as a neck mass but in our case it presented as a mediastinal mass, which is a very rare clinical presentation. Surgical excision is the mainstay of treatment. To the surgeon, the embryology and anatomy should be absolutely clear as dissection may be challenging due to the close proximity and variable course of the cystic stalk to major neck vessels and nerves.